ESP Needs Analysis for Marketing Students in an Indonesian Vocational School: Insights from Strategy Analysis - LD. Dian Hidayat (Departement of Mathematics Education, 2024)
English for Specific Purposes (ESP) is essential in vocational education, tailoring language learning to meet professional needs. This research employed strategy analysis to explore ESP needs among 50 marketing students at SMKN 1 Bone, Indonesia. The data were collected using a questionnaire distributed via Google Forms during class hours and analyzed using descriptive statistics. The findings revealed strong preferences for interactive and career-oriented learning methods, emphasizing practical language applications. Students prioritized materials on product management and marketing strategy, favored group work, and highlighted reading as the most crucial sub-skill. Motivations for learning English included personal growth, career advancement, and international opportunities, underscoring the need to align curriculum with student preferences. Therefore, integrating student-centered approaches into ESP curriculum development is crucial for enhancing relevance and effectiveness. Future research is expected to explore longitudinal studies tracking language proficiency, comparative analyses across vocational schools for cultural insights, and evaluations of learning activities and motivational factors to enhance ESP education, ensuring students acquire essential language skills for global success